Protection from cigarette smoke‐induced vascular injury by recombinant human relaxin‐2 (serelaxin). Issue 5 (24th February 2016) - Pini, Alessandro; Boccalini, Giulia; Baccari, Maria Caterina; Becatti, Matteo; Garella, Rachele; Fiorillo, Claudia; Calosi, Laura; Bani, Daniele; Nistri, Silvia
Abstract: Smoking is regarded as a major risk factor for the development of cardiovascular diseases (CVD). This study investigates whether serelaxin (RLX, recombinant human relaxin‐2) endowed with promising therapeutic properties in CVD, can be credited of a protective effect against cigarette smoke (CS)‐induced vascular damage and dysfunction. Guinea pigs exposed daily to CS for 8 weeks were treated with vehicle or RLX, delivered by osmotic pumps at daily doses of 1 or 10 μg. Controls were non‐smoking animals. Other studies were performed on primary guinea pig aortic endothelial (GPAE) cells, challenged with CS extracts (CSE) in the absence and presence of 100 ng/ml (17 nmol/l) RLX. In aortic specimens from CS‐exposed guinea pigs, both the contractile and the relaxant responses to phenylephrine and acetylcholine, respectively, were significantly reduced in amplitude and delayed, in keeping with the observed adverse remodelling of the aortic wall, endothelial injury and endothelial nitric oxide synthase (eNOS) down‐regulation. RLX at both doses maintained the aortic contractile and relaxant responses to a control‐like pattern and counteracted aortic wall remodelling and endothelial derangement. The experiments with GPAE cells showed that CSE significantly decreased cell viability and eNOS expression and promoted apoptosis by sparkling oxygen free radical‐related cytotoxicity, while RLX counterbalanced the adverse effects of CSE. These findings demonstrate that RLX is capable of counteracting CS‐mediated vascular damage and dysfunction by reducing oxidative stress, thus adding a tile to the growing mosaic of the beneficial effects of RLX in CVD.